2019
DOI: 10.1093/jee/toz174
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Apis cerana Sacbrood Virus (AcSBV) Prevalence in Apis cerana (Hymenoptera: Apidae) in Northern Taiwan and Demonstration of its Infection in Apis mellifera (Hymenoptera: Apidae)

Abstract: Since 2016, Apis cerana sacbrood virus (AcSBV) has been recorded in Taiwan. It is epizootic in Apis cerana (Hymenoptera: Apidae) and causing serious loss of A. cerana. Herein, we performed a long-term survey of AcSBV prevalence in the populations of A. cerana in Northern Taiwan from January 2017 to July 2018. The surveillance of AcSBV prevalence in A. mellifera (Hymenoptera: Apidae) populations was starting and further confirmed by sequencing since April 2017; thus, these data were also included in this survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…In Taiwan, most A. cerana populations are reared in Northern Taiwan, and according to our observations, some of these apiaries are crossbreeding with A. mellifera populations. The detection of AcSBV prevalence in A. mellifera populations from the sampling sites where A. cerana and A. mellifera were crossbreeding confirmed that AcSBV prevalence rates gradually developed a similar trend in the A. cerana and A. mellifera crossbreeding apiaries, and the existence of AcSBV cross-infection between A. cerana and A. mellifera was also confirmed by phylogenetic analysis based on partial VP1 sequences [33]. Similar to our case, some SBV strains from A. mellifera included in this study were found to be distinct from other AmSBV strains in terms of genomic features and were clustered with AcSBVs based on whole genome comparisons and phylogenetic analysis [24,30,36,40].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…In Taiwan, most A. cerana populations are reared in Northern Taiwan, and according to our observations, some of these apiaries are crossbreeding with A. mellifera populations. The detection of AcSBV prevalence in A. mellifera populations from the sampling sites where A. cerana and A. mellifera were crossbreeding confirmed that AcSBV prevalence rates gradually developed a similar trend in the A. cerana and A. mellifera crossbreeding apiaries, and the existence of AcSBV cross-infection between A. cerana and A. mellifera was also confirmed by phylogenetic analysis based on partial VP1 sequences [33]. Similar to our case, some SBV strains from A. mellifera included in this study were found to be distinct from other AmSBV strains in terms of genomic features and were clustered with AcSBVs based on whole genome comparisons and phylogenetic analysis [24,30,36,40].…”
Section: Discussionsupporting
confidence: 56%
“…AcSBV has recently been recorded in Taiwan and caused serious losses of A. cerana from 2015 to 2019 [33][34][35]. In Taiwan, most A. cerana populations are reared in Northern Taiwan, and according to our observations, some of these apiaries are crossbreeding with A. mellifera populations.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations